(untitled) (Research, Society and Development, 2025)
This study aims to understand the combinations of conditions that constitute territorial hospitality in the region, contributing to broaden the understanding of hospitality as a cultural, relational, and situated practice, reinforcing its role in the construction of sustainable tourist destinations that are rooted in their territories. A qualitative-comparative approach was adopted, applying the Qualitative Comparative Analysis (QCA) method, specifically the crisp-set variant (csQCA), suitable for identifying multiple causal configurations based on binarized qualitative data. Data was collected through semi-structured interviews, direct observation, and document analysis, prioritizing restaurants with explicit connections to territory, culture, and sustainability. The findings revealed that authentic tourist experiences depend on the combination of sociocultural conditions and institutional practices. Relational hospitality, appreciation of local food culture, the presence of storytelling, use of regional ingredients, and sustainable practices are synergistic factors that enhance the perceived authenticity and the image of the destination as a “lived place.” The main limitation lies in the small sample size and the territorial focus on Serra da Canastra, which restricts generalization. Nevertheless, the configurational approach contributes to broadening the theoretical scope of hospitality in tourism by proposing a relational and territorialized understanding of the phenomenon.